(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
In dangerous working environments such as a Chemical, Biological and Radiological (CBR) exercise, a protective suit plays an important role to increase work efficiency as well as prevent fatal damages. Air gaps entrapped in protective suit play an especially important role in heat transfer. The distribution and size of air gaps depends on body motions. The study developed 8 representative body motions (stretching, walking, crawling, crouching, twisting, climbing and reaching, moving weights and lateral bending) of CBR exercises of which 2 ∼ 4 static body postures per each motion were derived. 3D body scan was conducted on one male participant for the postures listed. Scanning was performed on both nude and dressed bodies to measure the distribution and size of air gaps between human body and clothing. As a result, curves and volume of the air gaps varied with the different postures. The results serve as the basic data to improve protective performance of current protective suit.